2017
DOI: 10.1111/head.13082
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin and Migraine Headache

Abstract: This article reviews material presented at the 2016 Scottsdale Headache Symposium. This presentation provided scientific results and rationale for the use of intranasal oxytocin for the treatment of migraine headache. Results from preclinical experiments are reviewed, including in vitro experiments demonstrating that trigeminal ganglia neurons possess oxytocin receptors and are inhibited by oxytocin. Furthermore, most of these same neurons contain CGRP, the release of which is inhibited by oxytocin. Results ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
87
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(95 citation statements)
references
References 30 publications
4
87
0
Order By: Relevance
“…Harnessing the central OT system has been identified as a promising strategy in translational neuroscience for the development of targeted pharmacological interventions to improve outcome in several conditions currently lacking efficacious treatments (e.g. autism spectrum disorder 7 , schizophrenia 8 , migrain 9 , stroke 6 , obesity 10 , Prader-Willi 11 ).…”
mentioning
confidence: 99%
“…Harnessing the central OT system has been identified as a promising strategy in translational neuroscience for the development of targeted pharmacological interventions to improve outcome in several conditions currently lacking efficacious treatments (e.g. autism spectrum disorder 7 , schizophrenia 8 , migrain 9 , stroke 6 , obesity 10 , Prader-Willi 11 ).…”
mentioning
confidence: 99%
“…Neumann et al 30 recently demonstrated an uptake of OT in the brain after intranasal administration by way of microdialysis. Similarly, we have recently demonstrated that nasally applied radiolabeled oxyocin concentrates in the brain, but mainly in the trigeminal system of rats . There are three proposed ways how intranasally administered OT reaches its target areas: (1) intra‐axonal transport mechanisms, (2) via the peripheral blood stream and the unexpected crossing blood brain barrier, and (3) perineurally along peripheral nerve bundles to reach the CNS.…”
Section: Introductionmentioning
confidence: 98%
“…Similarly, we have recently demonstrated that nasally applied radiolabeled oxyocin concentrates in the brain, but mainly in the trigeminal system of rats. 31 There are three proposed ways how intranasally administered OT reaches its target areas: (1) intra-axonal transport mechanisms, (2) via the peripheral blood stream and the unexpected crossing blood brain barrier, and (3) perineurally along peripheral nerve bundles to reach the CNS. In a review of the existing literature it is concluded that the perineural mechanism is the most likely.…”
Section: Introductionmentioning
confidence: 99%
“…Robust evidence from studies in preclinical models has demonstrated the importance of the central OT system in the development (3) and regulation of complex social behaviours (4,5), the modulation of pain processing (6), feeding behaviour (7) and neuroinflammation after brain ischemia (8). Harnessing the central OT system has been identified as a potential strategy for the development of targeted pharmacological interventions to help to improve outcome in several conditions for which efficacious treatments do not currently exist (e.g autism spectrum disorder (9), schizophrenia (10), migraine (11), stroke (8), obesity (12), Prader-Willi (13)).…”
mentioning
confidence: 99%